Textile Messages : Inscribed Fabrics from Roman to Abbasid Egypt - Fluck, Cäcilia; Helmecke, Gisela (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
The practice to supply textiles with inscriptions is well known in Egypt from Pharaonic times onwards. Nevertheless systematic studies on inscribed fabrics have been neglected until the middle of the 1990s when they almost simultaneously caught the interest of various scholars. This richly illustrated volume is a first compilation of what is known on the subject so far. It concentrates on textiles of the first millennium AD, a period of changing cultures, religions and languages in Egypt, mirrored by the Greek, Coptic and Arabic inscriptions on the fabrics. The emphasis lies on the historical, linguistic, sociological and artistic aspects of these textiles. Numerous fabrics from international collections are introduced. Further articles deal with the radiocarbon dating and technical aspects.